To Compare the Efficacy of Tamsulosin, Solifenacin and Combination of Both in the Treatment of Double-J Stent Related Irritative Lower Urinary Tract Symptoms and Low Back Pain - Tareq, AHM Imrul; Islam, Md Sayedul (Bangladesh Journal of Urology, 2020)
Background: Stent-associated symptoms can have a significant impact on patient quality of life. Hematuria, urgency, frequency, dysuria, and both bladder and flank pain are the most prevalent symptoms related to indwelling ureteral stents. Among them irritative lower urinary tract symptoms and low back pain are more frequent. Despite the stent related symptoms, because of its importance stent is being kept in situ with varieties of medication. Several alpha-adrenergic blocker and antimuscarinic drugs are used to relief these symptoms like Tamsulosin, Solifenacin, Alphazosin etc. Both Tamsulosin and Solifenacin are not costly as use daily single dose. So combination of Tamsulosin and Solifenacin may act as a reliever of stent related symptoms and also cost effective. Methods and materials: For this purpose, a total of 126 patients having unilateral double-J ureteral stent for 7 days with stent related irritative LUTS and low back pain were included in this study. This hospital based prospective randomized clinical trial was carried out in Urology department of Bangabandhu Sheikh Mujib Medical University, Dhaka, during January 2014 to June 2015, to compare the irritative IPSS, improvement of quality of life score component of IPSS ,the low back pain score for double-J ureteral stent using Tamsulosin, Solifenacin and combination of both (Tamsulosin and Solifenacin) Results: Regarding the irritative sub group of International Prostate Symptom Score (IPSS) was observed during 2nd and 4th weeks follow up IPSS was significantly (p<0.05) higher in solifenacin and Tamsulosin group with compared to Tamsulosin+Solifenacin group. During 4th weeks follow up the mean quality of life (QOL) score was significantly (p<0.05) higher in solifenacin group and Tamsulosin group with compared to Tamsulosin+Solifenacin group.During 2nd weeks and 4th weeks follow up visual Analogue Pain Scale (VAPS) was significantly (p<0.05) higher in solifenacin group followed by Tamsulosin group and Tamsulosin+Solifenacin group. Conclusion: Combined use of Tamsulosin and Solifenacin is more effective than use of single drug (either Tamsulosin or Solifenacin) in the treatment of ureteral double-J stent related irritative LUTS and low back pain. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.48-51